The Influence Of Price And Creativity On Customer Satisfaction At Sumbul Flower Market’s - Kaban, Debi Yolanda; Khalishah, Khansa; Nasution, Ika Dama Yanti (Jurnal Ilmu Ekonomi dan Bisnis, 2025)
One of the Micro, Small and Medium Enterprises that is currently trending and developing is the flower business. Every flower entrepreneur must be able to manage their business strategy, both in terms of price, creativity, service, innovation and other strategies that can increase sales, win the competition and provide value to consumers according to consumer expectations. This study aims to determine the effect of price and creativity on consumer satisfaction in the Sumbul flower market. The sampling technique used in this study was purposive sampling with the accidental sampling method. The research sample consisted of 100 respondents who were flower consumers in the Sumbul flower market. The processing of research data was assisted by the SPSS. The results of the study showed that price had a significant effect on consumer satisfaction in the Sumbul flower market. Creativity had a significant effect on consumer satisfaction in the Sumbul flower market.